The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s10734-019-00421-4
|View full text |Cite
|
Sign up to set email alerts
|

Institutional perspectives in transition: research groups’ profiles and embeddedness in organisational and national context

Abstract: Research into differentiation and profiling of knowledge producing institutions through the lenses of institutional logics and field embeddedness have proliferated in recent years. By discussing this process in the context of research groups, as those basic units in which knowledge production epistemically and practically takes place, this article offers a contribution to the theoretical discussion on organisational differentiation. Based on a small-N comparative case study of research groups operating in diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 67 publications
1
11
0
Order By: Relevance
“…Our preconception was that we should find more differences among the research groups in different types of organisations in a given country, versus among the research groups in a given organisational context but in different countries. However, we discovered that neither the organisational context nor the country context clearly determined the profiles (Nokkala & Diogo, ). Thus, although the typology of profiles can in itself be an interesting tool, we could not advance beyond the typology to more explanatory findings using the conventional approach of predetermined comparative criteria.…”
Section: A Conventional and Then Inverted Comparison Of Research Groumentioning
confidence: 99%
See 4 more Smart Citations
“…Our preconception was that we should find more differences among the research groups in different types of organisations in a given country, versus among the research groups in a given organisational context but in different countries. However, we discovered that neither the organisational context nor the country context clearly determined the profiles (Nokkala & Diogo, ). Thus, although the typology of profiles can in itself be an interesting tool, we could not advance beyond the typology to more explanatory findings using the conventional approach of predetermined comparative criteria.…”
Section: A Conventional and Then Inverted Comparison Of Research Groumentioning
confidence: 99%
“…The empirical case application is based on a comparison of 11 research groups in three small European countries. The aim of our study (reported in Nokkala & Diogo, ) was to examine how research groups operating in the policy‐relevant interdisciplinary research field, nanosciences, perceive the mission and beneficiaries of their work, and organise their work and collaborations. These groups work in varying organisational contexts and in three countries.…”
Section: A Conventional and Then Inverted Comparison Of Research Groumentioning
confidence: 99%
See 3 more Smart Citations